Annual Plant Reviews 2010
DOI: 10.1002/9781444391015.ch6
|View full text |Cite
|
Sign up to set email alerts
|

Glycosyltransferases of the GT8 Family

Abstract: The higher plant genomes sequenced to date include numerous genes encoding proteins classifi ed as belonging to CAZy family GT8. The large number and diversity of GT8 proteins in higher plants, which currently constitute more than 65% of the identifi ed eukaryotic GT8 genes, highlight the importance of these proteins in plants. Here we summarize a detailed phylogenetic study of GT8 proteins from three monocot and four dicot plant genomes that clearly divides higher plant GT8 proteins into two distantly related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 99 publications
(160 reference statements)
2
13
0
Order By: Relevance
“…The different pattern of [Me]GlcA decorations mediated by the GUX1 and GUX2 transferases might be a property of the enzymes themselves. Analysis of the GUX clade of the GT8 family shows that these proteins are phylogenetically divergent (Figure S1; Yin et al ., , ), consistent with the finding that they have different roles in planta . The different patterns of activity are not a consequence of different expression time or tissue of GUX1 or GUX2, as the correct pattern of decorations was recreated in the complemented gux1 gux2 mutant when GUX1 or GUX2 were expressed under an identical promoter.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The different pattern of [Me]GlcA decorations mediated by the GUX1 and GUX2 transferases might be a property of the enzymes themselves. Analysis of the GUX clade of the GT8 family shows that these proteins are phylogenetically divergent (Figure S1; Yin et al ., , ), consistent with the finding that they have different roles in planta . The different patterns of activity are not a consequence of different expression time or tissue of GUX1 or GUX2, as the correct pattern of decorations was recreated in the complemented gux1 gux2 mutant when GUX1 or GUX2 were expressed under an identical promoter.…”
Section: Discussionsupporting
confidence: 89%
“…To determine whether these enzymes are evolutionarily divergent or encoded by more recently duplicated genes, the conserved catalytic domains of the five Arabidopsis glycosyltransferase family 8 (GT8; Cantarel et al ., ) GUX proteins and orthologues from nine fully sequenced plant genomes were aligned and used to build a phylogenetic tree (Figure S1). GUX1 and GUX2 are found in different clades, a finding consistent with trees generated from full length proteins (Mortimer et al ., ; Yin et al ., , ). This divergence seems to pre‐date the separation of the monocot and dicot lineages, and suggests that GUX1 and GUX2 may perform different functions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is homologous to the PGSIP based on MSU rice genome annotation (Ouyang et al, 2007). It is believed that PGSIP is possibly involved in the initiation of the synthesis of amylopectin in a manner analogous to glycogenin enzymes (Yin et al, 2010). Glycogenins are self-glycosylating proteins in fungal and mammalian systems crucial in initiating glycogen synthesis by forming short MOS primers (Smythe and Cohen, 1991;Roach et al, 2012).…”
Section: Discussion Starch Structure Implication To Tweak Cooking Quamentioning
confidence: 99%
“…To predict the hydrophobic sensing sites, a homology model of the C-terminal catalytic domain of UGGT1 was constructed based on the crystal structures of other glycosyltransferases belonging to the CAZy family GT8. 34) Comparison of the predicted threedimensional structure with hydropathy plots suggested that the hydrophobic peptide cluster (residues 1340-1349) is exposed on the surface, whereas the hexapeptide (residues 1417-1422) is buried inside. Although it is currently impossible to conclude that the hydrophobic peptide clusters serve as a folding sensor, the decapeptide (residues 1340-1349) sequence (ILFLDVLFPL) appears to be important because of its high level of conservation in eukaryotes.…”
Section: -32)mentioning
confidence: 99%